Disrupting the disruption cycle – A longitudinal analysis of aggression trajectories, quality of life, psychopathology and self-efficacy in closed youth residential care. (June 2020) - Kind, Nina; Bürgin, David; Clemens, Vera; Jenkel, Nils; Schmid, Marc
Highlights: Stable-high aggressive behavior coincides with more placement disruptions. Aggression is less likely when life quality, drug use and suicide ideation improve. Interdisciplinary approaches that cultivate youths' self-efficacy may be effective. Abstract: Background: A substantial amount of youths living in youth residential care demonstrate clinical levels of aggression during the course of their placements, which poses a major risk to care continuity. Yet developmental trajectories of aggressive behavior can vary. Objective: We investigated if changes in quality of life (QoL), psychopathological symptoms and perceived self-efficacy predict aggressive behavior trajectories in youths with clinical aggression levels living in closed youth residential care in Germany. Method: Youths (n = 63; 76.2% female; ages 11–17, M = 14.4, SD = 1.30) answered well-established questionnaires at two data collection points (T1 and T2) over an average of 6.5 months. Professional caregivers rated youths' aggressiveness in the 'aggressive behavior' subscale of the Child Behavior Checklist (CBCL). Two trajectories were retrospectively identified for youths demonstrating aggressive behavior at or above the borderline clinical range – 'stable-high' trajectories with persevering aggressive behavior ratings (CBCL T ≥ 67 at T2) and 'improved' trajectories with improved aggressive behavior ratings (CBCL T < 67 at T2). We conducted binary logistic regression analyses to calculate if changes in self-reported QoL, psychopathology and perceived self-efficacy might predict trajectories of aggressive behavior. Results: Youths were more likely to belong to the 'improved' than 'stable-high' aggressive behavior trajectory if they reported greater QoL improvements in regards to relationship with peers ( B = 0.89, SE = 0.45, p = 0.014) and managing school requirements ( B = 0.69, SE = 0.69, p = 0.010), greater reductions in substance use ( B = −0.26, SE = 0.16, p = 0.029) and suicide ideation ( B = −0.32, SE = 0.17, p = 0.020), as well as improvements in perceived self-efficacy, dependent on initial aggression level ( B = 0.05, SE = 0.03, p = 0.034). Those with 'improved' trajectories were also less likely to experience placement disruptions. Conclusion: In light of our exploratory findings, incorporating various life domains into closed residential care plans, focusing on emotion regulation, substance use prevention, and providing an environment that encourages self-efficacy could reduce aggressive behavior and subsequent placement disruptions. Implications for youth welfare policy and future research are discussed.